Pengaruh Senam Tera Terhadap Tingkat Kecemasan Ibu Hamil Trimester III Menghadapi Persalinan - Lestari, Ayu Fuzi; Yuliana, Yuliana; Amaliyah, Salmah; Putriastuti, Widya; Juaeriah, Ryka (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
According to WHO (2020) around 10% of pregnant women experience depression and this condition is higher in developing countries, reaching 15.6% during pregnancy and 19.8% after childbirth. Anxiety experienced during pregnancy can have negative consequences for both the mother and the fetus. This unfavorable impact is not only during pregnancy but can also affect the process of childbirth and lactation. There are various kinds of exercise to reduce anxiety, one of which is gymnastics. One type of exercise that is effective for reducing anxiety is tera exercise. Terra gymnastics is a breathing exercise combined with movement and adopted from Tai Chi exercises. All movements in tera exercise can reduce anxiety, stress, and reduce levels of depression. Currently researchers are doing it on pregnant women aiming to control the level of anxiety facing the birth process using movements that are safe for pregnant women, especially breathing technique exercises. The aim of the study was to determine the effect of tera exercise on reducing the anxiety level of pregnant women facing childbirth. The research method used is a true experiment with a pretest-posttest approach without a control group design. The research respondents used a purposive sampling technique by means of random sampling, totaling 30 pregnant women as respondents in the working area of the Batujajar Health Center. Data analysis using univariate and bivariate with Marginal homogeneity test. The results showed that of the 30 respondents before the intervention, there were 27 people (90%) who had moderate anxiety levels and 3 people (10%) had severe anxiety levels. After being given the intervention, 16 people (53.3%) had no symptoms, 12 people (40.0%) had moderate anxiety and 2 people (6.7%) had moderate anxiety, and none of them had severe anxiety (0%). Bivariate analysis obtained the results of p value = 0.000 <0.05, Ho was rejected, it was concluded that there was an effect of intervention on anxiety levels.